2014
DOI: 10.5717/jenb.2014.18.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training is more effective than resveratrol supplementation on alleviation of inflammation in peritoneal macrophages of high fat diet mice

Abstract: [Purpose]This study investigated the effect of exercise training and resveratrol supplementation with low fat diet on proinflammatory profiles by Lipopolysaccharide (LPS)-stimulation in peritoneal macrophage of high fat diet mice.[Methods]To accomplish the purpose of this study, C57BL/6 male mice were fed high fat diet (45% fat diet) for 8 weeks. Then these mice were divided into 3 groups; HLC (high fat diet and low fat diet for 8 weeks as the control, n=10), HLR (high fat diet and low fat diet for 8 weeks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…ICR mice (n = 6/group/treatment/experiment) were injected intraperitoneally with 2 mg BCG (Shanghai Institute of Biological Products) or PBS on day 2 and day 10. Peritoneal exudate cells were harvested from these mice, and peritoneal macrophages were purified on days 4, 8, and 12 by washing cells from peritoneal cavity lavage with 5 ml of ice-cold, sterile PBS, according to a previously described protocol ( Park et al, 2014 ). The cells were distributed in DMEM supplemented with 10% FBS in six-well tissue culture plates (5 × 10 6 cells/ml) and incubated for 4 h. Non-adherent cells were removed by washing twice with Opti-MEM at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…ICR mice (n = 6/group/treatment/experiment) were injected intraperitoneally with 2 mg BCG (Shanghai Institute of Biological Products) or PBS on day 2 and day 10. Peritoneal exudate cells were harvested from these mice, and peritoneal macrophages were purified on days 4, 8, and 12 by washing cells from peritoneal cavity lavage with 5 ml of ice-cold, sterile PBS, according to a previously described protocol ( Park et al, 2014 ). The cells were distributed in DMEM supplemented with 10% FBS in six-well tissue culture plates (5 × 10 6 cells/ml) and incubated for 4 h. Non-adherent cells were removed by washing twice with Opti-MEM at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The regulation of pro‐inflammatory cytokines and enzymes by resveratrol is not well documented in hyperalgesia. However, earlier reports show that resveratrol did not affect secretion of pro‐inflammatory cytokines in peritoneal macrophages in different pathological conditions (Park et al, ; Wadsworth and Koop, ).…”
Section: Resultsmentioning
confidence: 78%
“…Similarly, it was reported that RES administration did not boost treadmill stamina over the 12-week training period in mice specifically bred for low-capacity exercise types (47). In contrast to exercise, RES supplementation did not affect peritoneal macrophages in mice (53). An overall evaluation of these results (all of which are animal experiments) indicates that the performance-boosting effects of RES in exercise are inconsistent.…”
Section: Res and Exercise In Experimental Animalsmentioning
confidence: 88%